Heightened response of eosinophilic asthmatic patients to the CRTH2 antagonist OC000459. Issue 9 (14th July 2014) - Pettipher, R.; Hunter, M. G.; Perkins, C. M.; Collins, L. P.; Lewis, T.; Baillet, M.; Steiner, J.; Bell, J.; Payton, M. A.
Abstract Background The CRTH2 antagonist OC000459 has previously been demonstrated to reduce airway inflammation and improve lung function in moderate persistent asthma. A study was conducted to determine the effect of lower once daily doses of OC000459 and to define the phenotype of subjects most responsive to treatment. Methods Adult subjects (percentage of predicted forced expiratory volume in 1 s (FEV1) 60–85%) were randomized to OC000459 at three dose levels (25 mg once daily, 200 mg once daily or 100 mg twice daily) or placebo for 12 weeks (n = 117–125 per group, full analysis set). The primary endpoint was the change from baseline in prebronchodilator FEV1, and secondary endpoints included Asthma Control Questionnaire (ACQ) and Standardised Asthma Quality of Life Questionnaire [AQLQ(S)], and incidence of exacerbations and respiratory tract infections. Results OC459 caused a significant improvement in FEV1 compared with placebo at a dose of 25 mg once daily (P = 0.028). A similar increase was observed in the other dose groups, and the mean change in FEV1 in the pooled dose groups at endpoint was 95 ml greater than placebo (P = 0.024). In a post hoc analysis of atopic eosinophilic subjects with uncontrolled asthma, a mean increase in FEV1 of 220 ml was observed compared with placebo (P = 0.005). The mean increase in FEV1 was more marked in younger subjects in this group: for subjects aged ≤40 years, there was a mean increase of 355 ml compared with placebo (P = 0.007). Improvements in ACQ and AQLQ(S) were observed in both the full analysis set and the atopic eosinophilic subgroup. There was a lower incidence of exacerbations and respiratory infections in subjects treated with OC000459. There were no drug‐related serious adverse events. Conclusions OC000459 is a safe and effective oral anti‐inflammatory agent, which achieved clinically meaningful improvements in lung function and asthma control in allergic asthmatics with an eosinophil‐dominant form of the disease. A dose of 25 mg given once daily was as effective as the higher doses studied.